IMPLEMENTASI RASPBERRY PI SEBAGAI PENERIMA STASIUN RADIO FM PADA FREKUENSI 87,9 MHz – 105,3 MHz MENGGUNAKAN RTL-SDR 2832U - Muhammad Danny Ramadhan Wibisono; Sigit Kusmaryanto; Ali Mustofa (Jurnal Mahasiswa TEUB, 2022)
In this modern era, the development of technology in the field of telecommunications is growing rapidly, especially with the needs of the global situation that relies more on long-distance communication. One of these developments is the emergence of the Raspberry Pi (Raspi) which is a single-board circuit (SBC) computer capable of being used as a medium for teleconferences, offices, Big Data, and high-resolution video players. The Raspberry Pi has advantages that resemble computers in general, everything in computer functions can also be done with the Raspberry Pi, but the Raspberry Pi has the advantage of being mini and portable. This study proposes the application of the Raspberry Pi 3b+ as a receiver for FM radio waves at a frequency of 87.9 MHz and 105.3 MHz using an RTL-SDR 2832U connected to a dipole antenna. The author uses signals from radio stations as transmitters of FM waves at frequencies of 87.9 MHz and 105.3 MHz. The implementation of the Raspberry Pi as an FM receiver in this study uses RTL-SDR 2832U with GNU Radio and GQRX software. The operating system used in this research is Raspberry Pi OS. The results show that the Raspberry Pi device can be used to receive FM waves at a frequency of 87.9 MHz and 105.3 MHz. The dipole antenna tested using VNA (Vector Network Analyzer) with a length of 81 cm for a frequency of 87.9 MHz and 66 cm for a frequency of 105.3 MHz and a linear antenna shape that can transmit signals with a VSWR of 1.29:1 at a working frequency of 87.96 MHz with a Return Loss of -23. dBm and 6 MHz bandwidth for 87.9 MHz frequency and 1.29:1 VSWR at 105.3.16 MHz working frequency with -29 dBm Return Loss and 8.4 MHz bandwidth for 105.3 MHz frequency. Keywords: Raspberry Pi, RTL-SDR, FM Signal, Software Defined Radio